Mineral and chemostratigraphy of a Toarcian black shale hosting Mn-carbonate microbialites (Úrkút, Hungary) - Polgári, M.; Hein, J.; Bíró, L.; Gyollai, I.; Németh, T.; Sajgó, C.; Fekete, J.; Schwark, Lorenz; Pál-Molnár, E.; Hámor-Vidó, M.; Vigh, T. (Elsevier BV, 2016)
© 2016 Elsevier B.V.Toarcian black shale that hosts Mn-carbonate microbialites at Úrkút, Hungary was investigated by mineralogical, inorganic, and organic geochemical methods for characterization and comparison with other European black shales representative of the Toarcian Oceanic Anoxic Event. Based on the authigenic mineral composition, calculations were made to estimate environmental conditions during sediment accumulation and early diagenesis. Geochemical and petrographic results of organic, carbonate, and REE multiple-proxy analyses revealed a strong congruence between the host black shale and the Mn-carbonate ore beds. The Úrkút black shale is really a gray shale with moderate to low TOC contents that accumulated in a starved basin. The organic matter and anoxic characteristics resulted from rapid accumulation of organic matter from microbial booms, accompanied by a geothermally generated hydrothermal circulation system, and a high rate of authigenic mineral formation (clay minerals and proto-ore minerals). The inferred enzymatic Mn and Fe oxidation blocked carbonate formation by decreasing the pH. The system remained suboxic via syngenetic mineral accumulation (Fe-rich biomats), and became anoxic during diagenesis in conjunction with pyrite generation. The separation of black shale beds and Mn-ore beds is not distinct through the section. Instead, a distal hydrothermally induced clay-rich authigenic assemblage (marlstone) best describes the black shale, in which Mn-oxide proto-ore beds (Mn-rich laminae) formed from the beginning of black shale deposition, when the oxygen supply in the sedimentary basin was insufficient for enzymatic Mn(II) oxidation. Mn-oxide proto-ore was transformed to Mn-carbonate ore during microbially mediated processes during early diagenesis. The drivers for Mn-bearing organic matter-rich marlstones were most probably a combination of regional and local processes, with generation of a tectonic rift system that promoted geothermally generated hydrothermal fluids, which initiated microbial blooms. Black shale mineralogy, geochemistry, and organic matter at Úrkút differ from those of the epicontinental shelf black shales of the Tethyan Ocean.